Low-dielectric lightweight high-temperature-resistant polyaryletherketone composite material and preparation method thereof

By adding pre-treated hollow microspheres and sulfonated PEEK to PAEK materials, and using segmented temperature rise molding technology, the problem of limited application of PAEK materials in the field of radomes is solved, and low dielectric, lightweight, and high temperature resistance are achieved. Aged composite materials improve radar sensor performance.

CN119320551AActive Publication Date: 2025-01-17江苏君华特种高分子材料股份有限公司 +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411567518.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-17
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The application of PAEK materials in the field of radar shields is limited, because ordinary modified plastics will slow down signal transmission speed, increase signal delay, and serious signal loss during radar wave transmission, affecting the performance of radar sensors.

Method used

By compounding pretreated hollow microbeads, sulfonated PEEK and polyaryl ether ketone matrix, the fluidity of the composite material is improved, and segmented temperature rise molding is used to prevent the migration and precipitation of hollow microbeads and achieve uniform dispersion in the matrix.

Benefits of technology

The realization of low-dielectric, lightweight, high-temperature aging-resistant composite materials ensures efficient propagation of radar waves, reduces energy loss, and improves the performance and precision of radar sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005119640970000061
    Figure BDA0005119640970000061
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, in particular to a low-dielectric lightweight high-temperature-resistant polyaryletherketone composite material and a preparation method thereof.The preparation method comprises the following steps that raw materials including sulfonated PEEK fine powder, hollow microspheres subjected to alkaline leaching pretreatment and polyaryletherketone fine powder are weighed; the raw materials are subjected to heat preservation and uniform premixing and then are subjected to sectional heat preservation compression molding to obtain the low-dielectric lightweight high-temperature-resistant polyaryletherketone composite material. The pretreated hollow microspheres, sulfonated PEEK and a polyaryletherketone matrix are compounded, so that the fluidity of the composite material is improved, meanwhile, migration and precipitation of the hollow microspheres can be effectively prevented through segmented heating and mold pressing, the problem of phase separation of the composite material is solved, and meanwhile, uniform dispersion of the hollow microspheres in the matrix is realized; therefore, the composite material with low dielectric, light weight and high-temperature aging resistance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material and a preparation method thereof. Background Art

[0002] As a high-performance thermoplastic polymer material, polyaryletherketone (PAEK) has good high-temperature aging resistance, chemical stability and excellent mechanical properties, which makes it have broad application prospects in aerospace, electronics, automobile manufacturing and other fields. However, the application of PAEK materials in high-tech fields is subject to certain restrictions, mainly due to its high dielectric constant.

[0003] In the field of intelligent driving, radar sensors are core components, and their performance directly affects the safety and reliability of intelligent driving. Most radar sensors are installed in the engine compartment, which means they need to work in a high-temperature, high-heat environment. In this case, the radar sensor needs a high-temperature resistant cover to protect it from sunlight and thermal environment. However, this cover must not only have high-temperature aging resistance, but also meet the high requirements of radar wave transmission.

[0004] Radomes have extremely high requirements for the transmittance and attenuation of radar waves. During the transmission of radar waves, ordinary modified plastics will cause the signal transmission speed to slow down, the signal delay to increase, and the signal loss to be serious, thus affecting the performance of radar sensors. This has limited the application of PAEK materials in the field of radomes. In order to solve this problem, researchers began to seek polyetheretherketone composite materials in order to achieve the goals of low dielectric constant, low dielectric loss, high transmittance, and high temperature aging resistance. Summary of the invention

[0005] In order to achieve the purpose of low dielectric, high transmittance, and high temperature aging resistance, the present invention provides a low dielectric, light, and high temperature resistant polyaryletherketone composite material and a preparation method thereof. The present invention improves the fluidity of the composite by compounding pretreated hollow microspheres, sulfonated PEEK, and a polyaryletherketone matrix. By performing segmented temperature increase molding, the migration and precipitation of hollow microspheres can be effectively prevented, and the phase separation problem of the composite can be solved while achieving uniform dispersion of hollow microspheres in the matrix, thereby obtaining a composite material with low dielectric, light weight, and high temperature aging resistance.

[0006] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:

[0007] A method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material comprises the following steps:

[0008] Weigh the raw materials according to weight: 5-15 parts of sulfonated PEEK fine powder, 10-20 parts of hollow microspheres pretreated by alkali leaching, and 65-85 parts of polyaryletherketone fine powder;

[0009] Premixing the raw materials evenly and then performing compression molding to obtain a low-dielectric, lightweight, and high-temperature-resistant polyaryletherketone composite material;

[0010] The compression molding is divided into five stages of heating, heat preservation and pressure preservation, each stage of temperature preservation is 5-10MPa, each stage of temperature preservation is 10-15min, and the heating rate is 3-5℃ / min:

[0011] The first section is heated to 350-360°C, the second section is heated to 361-370°C, the third section is heated to 371-380°C, the fourth section is heated to 381-390°C, and the fifth section is heated to 391-400°C.

[0012] Furthermore, the hollow microspheres are selected from hollow glass microspheres and / or hollow ceramic microspheres, and the average particle size of the combination of the two is not more than 60 μm, and the bulk density is not more than 0.6 g / cm 3 , compressive strength is at least 30MPa.

[0013] Furthermore, the hollow microspheres are selected from a combination of hollow glass microspheres and hollow ceramic microspheres, and the mass ratio of the hollow glass microspheres to the hollow ceramic microspheres is 2-5:1, such as the mass ratio of the hollow glass microspheres to the hollow ceramic microspheres is 4:1, or 5:1, or 5:2.

[0014] Furthermore, the alkaline leaching pretreatment process is: using a potassium hydroxide solution or a sodium hydroxide solution with a molar concentration of 1-5M to immerse the hollow microspheres at a constant temperature in the range of 50-100°C, stirring while immersing, with a stirring rate of 60-120rpm, and a immersion time of 1-3h.

[0015] Furthermore, the average particle size of the sulfonated PEEK fine powder is less than 120 μm; and the melt index of the sulfonated PEEK fine powder at 400° C. and a load of 2.16 kg is 30-40 g / 10 min.

[0016] Furthermore, the sulfonated PEEK fine powder is obtained by placing the PEEK fine powder in concentrated sulfuric acid and ultrasonically stirring it for 3-5 hours, wherein the ultrasonic stirring is carried out under heating conditions of 80-120° C. and the ultrasonic power is 20 Hz.

[0017] Furthermore, the average particle size of the polyaryletherketone fine powder is less than 120 μm; and the melt index of the polyaryletherketone fine powder at 400° C. and 2.16 kg load is 25-40 g / 10 min.

[0018] Further, the polyaryletherketone fine powder is selected from one or more of polyetheretherketone (PEEK), polyetherketone (PEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK) and polyetherketoneetherketoneketone (PEKEKK).

[0019] Furthermore, the premix is ​​mixed by a low-speed mixer, with a mixing rate lower than 350 rpm, a mixing time of 30-60 min, and a mixing temperature of 100-200°C.

[0020] Another aspect of the present invention provides a low-dielectric, lightweight, and high-temperature-resistant polyaryletherketone composite material obtained by the above-mentioned preparation method.

[0021] Beneficial technical effects:

[0022] The present invention uses alkali treatment to increase the active groups on the surface of the hollow microspheres, thereby increasing the oxygen content thereof. After mixing with sulfonated PEEK fine powder, the sulfonated PEEK surface has holes, which, on the one hand, provide anchoring points for a part of the microspheres, so that the filler is evenly dispersed, and on the other hand, the sulfonated PEEK acts with the hollow microspheres rich in hydroxyl groups on the surface to improve the compatibility of the polyaryletherketone matrix and the microsphere filler. The sulfonated PEEK plays a role of bridging the matrix and the filler, so that the polyaryletherketone matrix and the filler are more tightly fixed. In addition, the sulfonated PEEK can improve the fluidity of the matrix after compounding with the alkali-treated hollow microspheres.

[0023] Under the premise of ensuring stable mechanical properties, the present invention utilizes hollow microbeads impregnated with alkali solution and sulfonated PEEK fine powder to compound, and fully mixes the treated hollow microbeads, sulfonated PEEK fine powder and untreated polyaryletherketone fine powder through a mixer, thereby greatly improving the fluidity of the material. The present invention also adopts a segmented heating method for molding, which can effectively prevent the precipitation of low-density hollow glass microbeads or hollow ceramic microbeads, solve the phase separation problem of the composite material, and realize the uniform dispersion of the hollow microbeads in the matrix, so that the obtained composite material has lower dielectric properties and high-temperature aging resistance. The hollow structure of the hollow microbeads enables the composite material to have a micro-foaming effect, a low density and a high degree of lightweight. The composite material is applied to a radar detection system, and because it has the advantages of low density, low dielectric constant, high temperature resistance and the like, high-frequency radar waves can pass through without obstacles, thereby ensuring efficient propagation of the wave, reducing energy loss, and improving the detection performance and precision performance of the system. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.

[0026] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, the method is carried out in accordance with the general standard requirements or general methods.

[0027] Example 1

[0028] A method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material comprises the following steps:

[0029] S1. Alkaline immersion pretreatment of hollow microspheres: using 1M KOH solution to soak the hollow microspheres at a constant temperature of 60 minutes at 60°C, adding a rotor to stir while soaking, and the stirring rate is 150rpm. After soaking, the hollow microspheres are taken out and dried at 60°C, wherein the hollow microspheres are a combination of hollow glass microspheres and hollow ceramic microspheres, and the mass ratio of the hollow glass microspheres to the hollow ceramic microspheres is 4:1. At this mass ratio, the average particle size of the two after mixing is 40-60μm, and the bulk density is 0.3-0.6g / cm 3 The compressive strength of hollow glass microspheres is over 60MPa, and the compressive strength of hollow ceramic microspheres is 40MPa.

[0030] Preparation of sulfonated PEEK fine powder: PEEK fine powder (200 mesh) was placed in concentrated sulfuric acid (98wt%) and ultrasonically stirred at 80°C with an ultrasonic power of 20Hz. The reaction was stopped after 4 hours. After cooling to room temperature, the powder was washed with water until neutral and then vacuum dried at 240°C for 10 hours to obtain sulfonated PEEK fine powder. The melt index of the powder was measured to be 30g / 10min at 400°C and a load of 2.16kg.

[0031] S2. Weigh the raw materials: 50 g of sulfonated PEEK fine powder, 300 g of pretreated hollow microspheres, and 650 g of 200-mesh PEEK fine powder; premix the above raw materials at 200 rpm and 100°C for 30 min, perform a melt index test after mixing, and the melt index (400°C, 2.16 kg) is 38 g / 10 min, and then perform compression molding, wherein the compression molding is divided into five sections of heating, heat preservation and pressure preservation, each section has a temperature and pressure preservation of 5 MPa, each section has a temperature preservation of 10 min, and the heating rate is 5°C / min: the first section is heated to 360°C, the second section is heated to 370°C, the third section is heated to 380°C, the fourth section is heated to 390°C, and the fifth section is heated to 400°C. Observe in real time that the pressure drops and then replenish the pressure in time. After the mold temperature reaches the desired value, release the pressure repeatedly, and the staged heating is terminated. After naturally cooling to room temperature, demold the mold to obtain a low dielectric, lightweight, and high-temperature resistant polyaryletherketone composite material.

[0032] Example 2

[0033] A method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material comprises the following steps:

[0034] S1. Alkaline immersion pretreatment of hollow microspheres: using 2M KOH solution to soak the hollow microspheres at 80°C for 90 minutes, adding a rotor to stir while soaking, with a stirring rate of 150rpm, and taking them out after soaking and drying them at 80°C, wherein the hollow microspheres are a combination of hollow glass microspheres and hollow ceramic microspheres, the mass ratio of the hollow glass microspheres to the hollow ceramic microspheres is 5:1, and at this mass ratio, the average particle size of the two after mixing is 40-60μm, and the bulk density is 0.3-0.6g / cm 3 The compressive strength of hollow glass microspheres is over 60MPa, and the compressive strength of hollow ceramic microspheres is 40MPa.

[0035] Preparation of sulfonated PEEK fine powder: PEEK fine powder (300 mesh) was placed in concentrated sulfuric acid (98wt%) and ultrasonically stirred at 100°C with an ultrasonic power of 20Hz. The reaction was stopped after 4 hours. After cooling to room temperature, it was washed with water until neutral, and then vacuum dried at 240°C for 10 hours to obtain sulfonated PEEK fine powder. The melt index of the powder was measured to be 35g / 10min at 400°C and a load of 2.16kg.

[0036] S2. Weigh the raw materials: 200 g of sulfonated PEEK fine powder, 350 g of pretreated hollow microspheres, and 450 g of 300-mesh PEEK fine powder; premix the above raw materials at 250 rpm and 120°C for 45 min, perform a melt index test after mixing, and perform compression molding with a melt index (400°C, 2.16 kg) of 42 g / 10 min, wherein the compression molding is divided into five sections of heating, heat preservation, and pressure preservation, each section has a temperature and pressure preservation of 8 MPa, each section has a temperature and pressure preservation of 15 min, and a heating rate of 4°C / min: the first section is heated to 365°C, the second section is heated to 375°C, the third section is heated to 385°C, the fourth section is heated to 390°C, and the fifth section is heated to 395°C. Observe in real time that the pressure drops and then add pressure in time. After the mold temperature reaches the desired value, release the pressure repeatedly, and the staged heating is terminated. After naturally cooling to room temperature, demold the mold to obtain a low-dielectric, lightweight, and high-temperature resistant polyaryletherketone composite material.

[0037] Example 3

[0038] A method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material comprises the following steps:

[0039] S1. Alkaline immersion pretreatment of hollow microspheres: using 3M KOH solution to soak the hollow microspheres at a constant temperature for 120 minutes at 100°C, adding a rotor to stir while soaking, and the stirring rate is 200rpm. After soaking, the hollow microspheres are taken out and dried at 100°C, wherein the hollow microspheres are a combination of hollow glass microspheres and hollow ceramic microspheres, and the mass ratio of the hollow glass microspheres to the hollow ceramic microspheres is 5:2. At this mass ratio, the average particle size of the two after mixing is 40-60μm, and the bulk density is 0.3-0.6g / cm 3 The compressive strength of hollow glass microspheres is over 60MPa, and the compressive strength of hollow ceramic microspheres is 40MPa.

[0040] Preparation of sulfonated PEEK fine powder: PEEK fine powder (400 mesh) was placed in concentrated sulfuric acid (98wt%) and ultrasonically stirred at 120°C with an ultrasonic power of 20Hz. The reaction was stopped after 4 hours. After cooling to room temperature, the powder was washed with water until neutral and then vacuum dried at 240°C for 10 hours to obtain sulfonated PEEK fine powder. The melt index of the powder was measured to be 40g / 10min at 400°C and a load of 2.16kg.

[0041] S2. Weigh the raw materials: 150 g of sulfonated PEEK fine powder, 300 g of pretreated hollow microspheres, and 650 g of 300-mesh PEEK fine powder; premix the above raw materials at 300 rpm and 140°C for 60 min, perform a melt index test after mixing, and perform compression molding with a melt index (400°C, 2.16 kg) of 45 g / 10 min, wherein the compression molding is divided into five sections of heating, heat preservation, and pressure preservation, each section having a temperature and pressure preservation of 5 MPa, each section having a temperature and pressure preservation of 10 min, and a heating rate of 5°C / min: the first section is heated to 355°C, the second section is heated to 365°C, the third section is heated to 375°C, the fourth section is heated to 385°C, and the fifth section is heated to 395°C. Observe in real time that the pressure drops and then add pressure in time. After the mold temperature reaches the desired value, release the pressure repeatedly, and the staged heating is terminated. After naturally cooling to room temperature, demold the mold to obtain a low-dielectric, lightweight, and high-temperature resistant polyaryletherketone composite material.

[0042] Example 4

[0043] The preparation process and formula of this case are the same as those of Example 2, except that the hollow microspheres are only hollow glass microspheres.

[0044] Example 5

[0045] The preparation process and formula of this case are the same as those of Example 2, except that the hollow microspheres are only hollow ceramic microspheres.

[0046] Comparative Example 1

[0047] This case is a composite material of 900 g of PEEK fine powder and 100 g of sulfonated PEEK fine powder, and other operations are the same as those in Example 1.

[0048] Comparative Example 2

[0049] In this case, the hollow microbeads were not pretreated with alkali solution, and other operations were the same as those in Example 1.

[0050] Comparative Example 3

[0051] In this case, 1.5g of silane coupling agent KH560 and 3.0g of titanate coupling agent were used to pre-treat 150g of hollow microspheres (it can be wet treatment or dry treatment, wet treatment was selected in this case), and other operations were the same as in Example 1. The cost of hollow microspheres treated with coupling agents is 3-5 times higher than that of alkaline etching treatment, and the price is relatively high.

[0052] Comparative Example 4

[0053] In this case, sulfonated PEEK fine powder was not used, and other operations were the same as in Example 1.

[0054] Comparative Example 5

[0055] This case adopts a five-stage heating, heat preservation and pressure holding compression molding method. The temperature is directly raised to 400°C at a heating rate of 10°C / min, the pressure is maintained at 5MPa, and the holding time is 40min. Other operations are the same as Example 1.

[0056] The above cases were subjected to performance testing, and the test results are shown in Table 1 below.

[0057] Table 1 Performance of each case

[0058]

[0059] It can be seen from the above table that the combination of hollow glass microspheres and hollow ceramic microspheres has a beneficial effect on reducing the density of the composite and improving the melt index, so that the composite has a micro-foaming effect, low density, and high lightweight. Combined with the segmented temperature increase molding, it effectively prevents the precipitation of low-density hollow glass microspheres or hollow ceramic microspheres, solves the phase separation problem of the composite material, and realizes the uniform dispersion of the hollow microspheres in the matrix, so that the obtained composite has lower dielectric properties and high temperature aging resistance.

[0060] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material, characterized in that: The steps include: Weigh the raw materials according to weight: 5-15 parts of sulfonated PEEK fine powder, 10-20 parts of hollow microspheres pretreated by alkali leaching, and 65-85 parts of polyaryletherketone fine powder; Premixing the raw materials evenly and then performing compression molding to obtain a low-dielectric, lightweight, and high-temperature-resistant polyaryletherketone composite material; The compression molding is divided into five stages of heating, heat preservation and pressure preservation, each stage of temperature preservation is 5-10MPa, each stage of temperature preservation is 10-15min, and the heating rate is 3-5℃ / min: The first section is heated to 350-360°C, the second section is heated to 361-370°C, the third section is heated to 371-380°C, the fourth section is heated to 381-390°C, and the fifth section is heated to 391-400°C.

2. The method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material according to claim 1, characterized in that: The hollow microspheres are selected from hollow glass microspheres and / or hollow ceramic microspheres, with an average particle size of no more than 60 μm and a bulk density of no more than 0.6 g / cm 3 , compressive strength is at least 30MPa.

3. The method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material according to claim 2, characterized in that: The hollow microspheres are selected from a combination of hollow glass microspheres and hollow ceramic microspheres, and the mass ratio of the hollow glass microspheres to the hollow ceramic microspheres is 2-5:

1.

4. The method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material according to claim 1, characterized in that: The alkaline leaching pretreatment process is: using a potassium hydroxide solution or a sodium hydroxide solution with a molar concentration of 1-5M to immerse the hollow microspheres at a constant temperature within the range of 50-100°C, stirring while immersing, with a stirring rate of 60-120rpm, and a immersion time of 1-3h.

5. The method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material according to claim 1, characterized in that: The average particle size of the sulfonated PEEK fine powder is less than 120 μm; the melt index of the sulfonated PEEK fine powder at 400° C. and a load of 2.16 kg is 30-40 g / 10 min.

6. The method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material according to claim 5, characterized in that: The sulfonated PEEK fine powder is obtained by placing the PEEK fine powder in concentrated sulfuric acid and stirring it ultrasonically for 3-5 hours, wherein the ultrasonic stirring is carried out under heating conditions of 80-120° C. and the ultrasonic power is 20 Hz.

7. The method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material according to claim 1, characterized in that: The average particle size of the polyaryletherketone fine powder is less than 120 μm; the melting index of the polyaryletherketone fine powder at 400° C. and 2.16 kg load is 25-40 g / 10 min.

8. The method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material according to claim 7, characterized in that: The polyaryletherketone fine powder is selected from one or more of polyetheretherketone, polyetherketone, polyetherketoneketone, polyetheretherketoneketone and polyetherketoneetherketoneketone.

9. The method for preparing a low-dielectric, lightweight, high-temperature-resistant polyaryletherketone composite material according to claim 1, characterized in that: The premix is ​​mixed by a low-speed mixer, with a mixing rate lower than 350 rpm, a mixing time of 30-60 min, and a mixing temperature of 100-200°C. 10 . The low-dielectric, lightweight, and high-temperature-resistant polyaryletherketone composite material obtained by the preparation method according to claim 1 .

Citation Information

Patent Citations

  • Phosphorylation titanium dioxide hollow sphere-filled sulfonated polyether ether ketone film as well as preparation and application

    CN103304979A

  • Method for using niobium boride ceramic beads for preparation of high temperature high pressure resistant oil well cementation test block

    CN104326763A

  • Method for preparing reinforced phenolic aldehyde-epoxy resin composite material by utilizing hollow glass bead-carbon fiber sheet-glass fiber

    CN108976716A

  • Plate based on silicon-aluminum-based hollow microsphere material and production process of plate

    CN111909478A

  • Resin film, circuit board material, circuit board, and electronic apparatus

    JP2023081265A